2021
DOI: 10.1021/acssuschemeng.1c03452
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Kinetics of Phosphorus and Nitrogen in Iron-Rich Sewage Sludges during Hydrothermal Treatment and Recovery of Nutrients from Process Water

Abstract: Hydrothermal treatment (HT) is an emerging technique for sustainable sewage sludge management and resource recovery. Many sludges are rich in iron (Fe) due to the common addition of Fe salts in water resource recovery facilities. To develop guidance for reaction conditions targeting nutrient recovery, this study systematically investigated the influence of HT temperature, treatment time, and sludge source on the dynamic speciation evolution of phosphorus (P) and nitrogen (N) during HT of Fe-rich sewage sludge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
(154 reference statements)
2
16
0
Order By: Relevance
“…The HTL temperatures between 310 and 350 C and the reaction times between 15 and 60 min have been reported to maximize the biocrude yield and minimize the biocrude heteroatom content from a variety of feedstocks, [11][12][13][14] while homogeneous and heterogeneous catalysts have been reported to increase the carbon content in biocrude by catalyzing deoxygenation and denitrogenation reactions. [15][16][17][18] Another branch of HTL research has instead focused on recovering nutrients from HTL products in the form of inorganic fertilizers, for example, struvite (MgNH 4 PO 4 $6H 2 O) crystallization from the HTL-AP under alkaline conditions to produce a slow-release inorganic fertilizer providing plantavailable P, N, and Mg. 19,26,27 To maximize struvite production from the HTL-AP, nutrients in the feedstock should preferentially partition in the HTL-AP, where they tend to assume their bioavailable forms (e.g., NH 4 + , orthophosphates, K + , Ca 2+ , and Mg 2+ ) rather than accumulate in the hydrochar phase in their non-bioavailable forms (e.g., apatite phosphate, 19 calcite, 20 and vivianite 21 ). Since struvite formation is inhibited by the presence of Ca ions, the Ca concentration in the HTL-AP should be minimized, as it would cause the formation of a morethermodynamically stable hydroxyapatite (a less effective Pfertilizer).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HTL temperatures between 310 and 350 C and the reaction times between 15 and 60 min have been reported to maximize the biocrude yield and minimize the biocrude heteroatom content from a variety of feedstocks, [11][12][13][14] while homogeneous and heterogeneous catalysts have been reported to increase the carbon content in biocrude by catalyzing deoxygenation and denitrogenation reactions. [15][16][17][18] Another branch of HTL research has instead focused on recovering nutrients from HTL products in the form of inorganic fertilizers, for example, struvite (MgNH 4 PO 4 $6H 2 O) crystallization from the HTL-AP under alkaline conditions to produce a slow-release inorganic fertilizer providing plantavailable P, N, and Mg. 19,26,27 To maximize struvite production from the HTL-AP, nutrients in the feedstock should preferentially partition in the HTL-AP, where they tend to assume their bioavailable forms (e.g., NH 4 + , orthophosphates, K + , Ca 2+ , and Mg 2+ ) rather than accumulate in the hydrochar phase in their non-bioavailable forms (e.g., apatite phosphate, 19 calcite, 20 and vivianite 21 ). Since struvite formation is inhibited by the presence of Ca ions, the Ca concentration in the HTL-AP should be minimized, as it would cause the formation of a morethermodynamically stable hydroxyapatite (a less effective Pfertilizer).…”
Section: Introductionmentioning
confidence: 99%
“…, NH 4 + , orthophosphates, K + , Ca 2+ , and Mg 2+ ) rather than accumulate in the hydrochar phase in their non-bioavailable forms ( e.g. , apatite phosphate, 19 calcite, 20 and vivianite 21 ). Since struvite formation is inhibited by the presence of Ca ions, the Ca concentration in the HTL-AP should be minimized, as it would cause the formation of a more-thermodynamically stable hydroxyapatite (a less effective P-fertilizer).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on struvite crystallization kinetics from highly controlled synthetic solutions reported that crystallization at temperatures between 10 and 50 °C and alkaline pH between 8 and 10 combined with stirring at 100 to 300 rpm for 30 to 60 min recovers about 80–98% of P in the form of fine-sized struvite crystals. These studies assumed the absence of foreign ions, e.g., Ca 2+ , Fe 3+ , and Al 3+ , that can form other phosphate minerals, used low ionic strength (IS) solutions (IS < 0.1 M), and adopted controlled Mg/NH 3 –N/P ratios, e.g., regulated at equimolar or specific molar ratios, that assures the irreversibility and high selectivity of struvite formation . Unfortunately, these conditions are not found in actual HTL-AP product effluents, which contain significant concentrations of foreign ions and polar organic compounds, ,, higher ionic strength (0.2–0.4 M), , and nonequimolar Mg/NH 3 –N/P ratios. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, previous studies of the speciation of inorganics in hydrochar have only focused on the transformation of P during HTL of wet biomass wastes and have always assumed that P precipitates in hydrochar through the formation of apatite 20,43 (e.g., hydroxyapatite) and non-apatite inorganic phosphate minerals, e.g., vivianite, varulite, and strunzite. 44,45 These studies did not comprehensively assess the prole of P speciation in the aqueous phase (e.g., via functional group identication with 31 P NMR), ignoring the possibility of P precipitation by chemically bonding aqueous aromatics that are susceptible to repolymerization into hydrochar during HTL.…”
Section: Introductionmentioning
confidence: 99%